Masyarakat Pemberdayaan Masyarakat untuk Memanfaatkan Air Cucian Beras pada Budidaya Tanaman Sayuran di Kelurahan Karang anyar: Pemberdayaan Masyarakat untuk Memanfaatkan Air Cucian Beras pada Budidaya Tanaman Sayuran di Kelurahan Karanganyar - Neni Marlina; Marlina; Asmawati; Haperidah Nunilahwati; Keti Purnamasari; Gusmiatun; Maria Lusia; Dessy Tri Astuti; Berliana Palmasari (Altifani Journal: International Journal of Community Engagement, 2025)
Rice washing water (commonly called air leri) is a household waste that is often discarded, even though it can be used as a liquid organic fertilizer. This water contains a significant amount of essential nutrients such as nitrogen (N), phosphorus (P), potassium (K), vitamins, and minerals that support the growth of vegetable crops. When consumed by humans, it may also improve overall health. The objective of this community service activity is to enhance public knowledge about the benefits of rice washing water for plant growth and human health, to encourage behavioral changes in environmentally friendly waste management, and to improve community skills in making and using rice washing water as a liquid organic fertilizer for home gardening. The method of implementation includes three main activities: (1) education and outreach on the benefits of rice washing water for plant growth, soil fertility, health, and environmental sustainability; (2) hands-on training to teach the community how to collect, store, and apply the water efficiently to vegetable crops; and (3) mentoring, by assisting residents in applying rice washing water to home garden plots. The results show that 75% of participants experienced increased understanding and skills in managing household waste into eco-friendly agricultural inputs. There was also increased interest in home gardening. This activity contributes to food security, family health, and the reduction of household waste.